John Steinbeck - unknown:::Creator::::::::::::
John Steinbeck on his Salinas High School basketball team. From left, front row: Church (forward), Captain Kellogg (forward), Eddie Johnson (guard); middle row: Bairos (guard), Storm (guard), W. Muller (forward, JS (forward); back row: Best (coach), Thorup (center), Black (center), Sherwood (guard), R. Muller (manager). His teammates later were reported to have said that he enjoyed basketball but wasn't very good at it.